Efektivitas Iklan YouTube dalam Meningkatkan Penerimaan Santri Baru di Pondok Pesantren Nurul Jadid - Misbahul Arifin; Faiq Julia Iqna’a; Abdul Majid; Achmad Faizal Ababil (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study focuses on the effectiveness of YouTube advertisements in increasing new student enrollment at Pondok Pesantren Nurul Jadid. The aim of this research is to examine the extent to which digital video content on the YouTube platform influences public perception, enrollment decisions, and the role of media in shaping the image of Islamic educational institutions. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with new students, parents, the new student admissions team (PSB), and the pesantren’s media division, as well as internal documentation of the registration process. The results show that YouTube advertisements have a significant impact on shaping positive public perceptions of Pondok Pesantren Nurul Jadid. Visual narratives, alumni testimonials, and authentic depictions of student life successfully attract the attention of prospective students and their parents, leading to an annual increase in enrollment numbers. Videos that are narratively designed and equipped with registration links have proven effective in guiding audiences from interest to concrete action. The implications of this study suggest that Islamic boarding schools need to adopt strategic digital marketing approaches to expand their outreach and strengthen institutional branding.